Differential capacitive sensor based interface circuit design for accurate measurement of water content in crude oil - Aslam, M.Z. (IEEE Computer Society, 2014)
In crude oil extraction and processing, measurement of water content plays vital role. Several methods are available to measure water content in crude oil but most of them are laborious and for offline detection. For an accurate online measurement of water content in crude oil, a novel interface circuit is proposed by using differential capacitive sensor based on modulation technique. This design consists of two capacitive sensors that compare the voltage signals of pure crude oil and solution under test. The simulation and experimental tests have been carried out to investigate the performance of the system. The interface circuit has sensitivity of 1.123mV/pF, which is adjustable according to the requirement. The system is tested for different concentrations of water and crude oil. The results showed that the proposed system has robust and near optimal performance with the change of water content in oil, which intern advantageous in term of accuracy and portability Â© 2014 IEEE.